2018
DOI: 10.1111/jog.13862
|View full text |Cite
|
Sign up to set email alerts
|

First trimester physiological development of the fetal foot position using three‐dimensional ultrasound in virtual reality

Abstract: Aim In anatomic studies of the embryo, it has been established that during the development of the lower limb, several changes in foot position can be observed defined as a temporary ‘physiological clubfoot’. The aim of this study was to develop and test a measurement tool for objective documentation of the first trimester foot position in vivo and made an attempt to create a chart for first trimester foot position. Methods We developed a virtual orthopedic protractor for measuring foot positioning using three‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 28 publications
0
11
0
1
Order By: Relevance
“…2,7,9 Before 13 weeks of gestation, a transient clubfoot position can be present as part of normal development. 10 To diagnose clubfoot, one must visualize both the tibia and fibula in the same plane as the sole of the foot (Figures 1 and 2). Abnormal positioning persists over the duration of the scan.…”
Section: Ultrasound Findingsmentioning
confidence: 99%
“…2,7,9 Before 13 weeks of gestation, a transient clubfoot position can be present as part of normal development. 10 To diagnose clubfoot, one must visualize both the tibia and fibula in the same plane as the sole of the foot (Figures 1 and 2). Abnormal positioning persists over the duration of the scan.…”
Section: Ultrasound Findingsmentioning
confidence: 99%
“…Bogers et al . showed that measurements of the embryonic foot position were feasible using 3D ultrasound datasets which were studied using VR 9 …”
Section: Introductionmentioning
confidence: 99%
“…Bogers et al showed that measurements of the embryonic foot position were feasible using 3D ultrasound datasets which were studied using VR. 9 From this background we hypothesize that embryonic posture at rest during the early prenatal period, even in uneventful pregnancies, will demonstrate already small variations, as a proxy for neurobehavior/ neurodevelopment. We therefore aim to assess feasibility and reproducibility of embryonic posture evaluation at rest at 9 (+0-6 days) weeks' GA using 4D ultrasound and VR techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Around 11th to 14th weeks of pregnancy Nuchal translucency (NT) is measured by sonography in fetus ( 10 ). The size of NT shows the amount of fluid behind the neck of the fetus.…”
Section: Introductionmentioning
confidence: 99%
“…The amount of fluid behind neck can be increased in fetus with normal karyotype. In this condition fetus is at a significant risk of still birth, heart defect, and delay in neurodevelopment ( 10 - 12 ).…”
Section: Introductionmentioning
confidence: 99%